Anabolic-Androgenic Steroids and Exercise Training: Breaking the Myths and Dealing With Better Outcome in Sarcopenia - Falqueto, Hugo; dos Santos, Marcelo Rodrigues; Manfredi, Leandro H. (Frontiers in Physiology, 2022)
Sarcopenia is an emerging clinical condition determined by the reduction in physical function and muscle mass, being a health concern since it impairs quality of life and survival. Exercise training is a well-known approach to improve physical capacities and body composition, hence managing sarcopenia progression and worsening. However, it may be an ineffective treatment for many elderly with exercise-intolerant conditions. Thus, the use of anabolic-androgenic steroids (AAS) may be a plausible strategy, since these drugs can increase physical function and muscle mass. The decision to initiate AAS treatment should be guided by an evidence-based patient-centric perspective, once the balance between risks and benefits may change depending on the clinical condition coexisting with sarcopenia. This mini-review points out a critical appraisal of evidence and limitation of exercise training and AAS to treat sarcopenia.